Illness Dreams and Medical Practices in the Song Dynasties - Lijun TANG (Yixue yu zhexue)
As the name suggests, "illness dreams" refer to dreams related to illness. In classical medical theory, such dreams were believed to reflect the physiological state of a person during illness. Functionally, divine imagery in illness dreams was thought to not only have healing effects, but also serve as a medium for spreading religious beliefs. Additionally, Confucian moral teachings were conveyed through these dreams. During the Song Dynasties, popular perceptions of illness dreams were deeply influenced by religious beliefs, differing significantly from the more rational interpretations of classical medical scholars. This contrast fundamentally reflects the scarcity of medical resources available to the common people in the Song Dynasties and their deep longing for effective treatment.